Co-occurrence of Peutz-Jeghers syndrome and unilateral multicystic dysplastic kidney: a case report - Yaqing Liu; Sunhe Hu; Yihan Gan; Yulan Fang (BMC Nephrology)
Abstract Background This case study aimed to evaluate the co-occurrence of Peutz-Jeghers syndrome (PJS) and unilateral multicystic dysplastic kidney (MCDK) disease through clinical and genetic analysis of a patient with both conditions. Case presentation A 13-year-and-7-month-old female patient presented with typical features of PJS, including pigmented polyposis of the gastrointestinal tract, dark pigmented spots on the skin, and a history of intestinal intussusception. Genetic testing revealed a pathogenic mutation in the serine/threonine protein kinase 11 (STK11) gene c.843del frameshift variant (p.L282Sfs*5), characterized by guanine deletion at position 843 resulting in leucine-to-serine substitution at residue 282, complete alteration of downstream amino acid sequence, and premature translation termination. In addition, she also presented with MCDK. Conclusion This case reveals a potential novel role of STK11 in renal embryogenesis, expanding its phenotypic spectrum and challenging the conventional paradigm that STK11 mutations solely confer tumor predisposition. Through comprehensive literature review, we propose three mechanistic hypotheses - “metabolo-developmental coupling disruption”, “ciliopathy-like pathogenesis”, and “epigenetic modulation of developmental plasticity” - providing new molecular insights into congenital renal anomalies. These findings warrant systematic renal evaluation in PJS patients and exploration of metabolism-targeted therapeutic strategies. Clinical trial number Not applicable.